Newly diagnosed seropositive rheumatoid arthritis in a 52-year-old man superimposed on long-standing ankylosing spondylitis during secukinumab treatment - Jaroslaw Nowakowski; Anna Tomoń; Dorota Telesińska-Jasiówka; Mariusz Korkosz (Central European Journal of Immunology, 2023)
Rheumatoid arthritis (RA) and ankylosing spondylitis (AS) are severe chronic inflammatory joint diseases with different immune-mediated mechanisms playing a role in their pathogenesis. Rheumatoid arthritis is an erosive arthritis of peripheral joints and AS is a spondyloarthropathy affecting mainly sacroiliac and spinal joints leading to excessive bone formation and ankylosis. The coexistence of RA and AS in the same patient is rare. Presented here is a 52-year-old patient with long-standing AS with bilateral ankylosis of sacroiliac joints who developed peripheral symmetric polyarthritis while being treated with the interleukin 17 inhibitor secukinumab introduced due to secondary inefficacy of the tumor necrosis a inhibitor etanercept. He was finally diagnosed with seropositive RA coexisting with AS and treatment was changed to the Janus kinase inhibitor tofacitinib. Eventually, remission was sustained with use of the interleukin 6 inhibitor tocilizumab. This is the first case of RA developing during anti-interleukin 17 therapy. Although tocilizumab lacks efficaciousness in AS, in this case therapy was succesful as the RA-driving cytokine mechanism possibly prevailed.